Energy scavenging using piezoelectric materials : a thesis presented in partial fulfillment of the requirements for the degree of Master of Engineering in Mechatronics at Massey University, Palmerston North, New Zealand - Liang, Huangbo (Massey University, 2008)
In recent years, wireless devices have been developing rapidly for various uses that run on batteries. However, when the devices are made smaller and the networks increase in number, it is not practical to replace the depleted batteries, such as in areas difficult to access. Alternative method is to scavenge power available in the environment where the wireless device is placed. This thesis is focused on scavenging power via vibrations as a power source. According to the literature piezoelectric material is the best choice to convert mechanical forces into electric field. Piezoelectric generator devices have been modelled and analyzed. A case study of power generator for use in traffic monitoring sensors is assumed. The thesis describes such a piezoelectric power generator, developed based on a cantilever beam and using modelling techniques available in literature. The design is optimized by Sequential Quadratic Programming method. A prototype of the generator is built and tested extensively. The generated power is stored in a specially built circuit. The experiments show that the prototype piezoelectric power generator can provide 0.09J in a simulated traffic scenario. Also the generated energy can be stored in the electric circuit which gives a stable 5 V DC output. It is noted that piezoelectric material is very brittle and was cracked during the experiment. As a consequence, the most of the experiment were conducted with a slightly modified generator. In conclusion, this thesis research has developed successfully both mathematical and a physical model of the piezoelectric power generator for wireless traffic monitoring sensors. Further work will still be in order in improving the current design.
Keywords: Piezoelectric devices; Detectors